Test studies on soil with cemented-soil piles under bidirectional cyclic loading. Issue 4 (13th November 2021) - Chen, Yiran; Wang, Jun; Zhu, Kai; Liu, Feiyu; Hu, Xiuqing; Fu, Hongtao
Abstract : Seismic load can cause a change in the strength and stiffness of composite foundations with cement–soil piles. In this study, cyclic simple shear tests were conducted on a composite soil with a cemented soil core to investigate the dynamic behaviour of the composite foundation under bidirectional cyclic loading. The specimens were first K 0 -consolidated and then sheared under different cyclic stress magnitudes and phase differences. The results showed that phase difference had an obvious influence on the dynamic strength of the composite soil: with an increase in the phase difference, the bidirectional shear strains were accelerated and the dynamic strength of the composite soil decreased. The hysteresis curve of the composite soil exhibited a greater inclination at a larger phase difference, which can be attributed to stiffness softening. The strength of composite soil can be significantly increased and stiffness softening can be limited by increasing the area replacement ratio.